2020
DOI: 10.1016/s0140-6736(20)30045-3
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional, and national burden of chronic kidney disease, 1990–2017: a systematic analysis for the Global Burden of Disease Study 2017

Abstract: Background Health system planning requires careful assessment of chronic kidney disease (CKD) epidemiology, but data for morbidity and mortality of this disease are scarce or non-existent in many countries. We estimated the global, regional, and national burden of CKD, as well as the burden of cardiovascular disease and gout attributable to impaired kidney function, for the Global Burden of Diseases, Injuries, and Risk Factors Study 2017. We use the term CKD to refer to the morbidity and mortality that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
1,733
3
33

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,816 publications
(1,927 citation statements)
references
References 86 publications
10
1,733
3
33
Order By: Relevance
“…Because the kidneys are involved in the regulation of many systemic processes, patients with CKD are at a high risk to develop multiple systemic complications, including rheologic, metabolic, immunologic, CV, and other disturbances [42]. Importantly, several of these complications show similarities with the ageing process, such as CV diseases (CVD), sarcopenia, bone disease, as well as frailty [43,44], cognitive dysfunction [44], immune deficiency [12], and finally mortality [1]. Thus, patients with CKD appear to have a highly accelerated ageing process as compared to healthy subjects or non-CKD patients.…”
Section: Premature Ageing In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the kidneys are involved in the regulation of many systemic processes, patients with CKD are at a high risk to develop multiple systemic complications, including rheologic, metabolic, immunologic, CV, and other disturbances [42]. Importantly, several of these complications show similarities with the ageing process, such as CV diseases (CVD), sarcopenia, bone disease, as well as frailty [43,44], cognitive dysfunction [44], immune deficiency [12], and finally mortality [1]. Thus, patients with CKD appear to have a highly accelerated ageing process as compared to healthy subjects or non-CKD patients.…”
Section: Premature Ageing In Ckdmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a major global health burden that contributes to increased morbidity and mortality in affected patients [1]. Inflammation is a key risk factor for CKD progression [2], and recent data from the CANTOS trial suggest that anti-inflammatory treatment in patients with CKD reduces major adverse cardiovascular events [3].…”
Section: Introduction-ckd Inflammation and Premature Ageingmentioning
confidence: 99%
“…However, a well-conducted cohort study in Taiwan showed that there is an increased risk of TB in early stage chronic kidney disease (CKD) [52], and it has been suggested that TB prevention efforts be targeted to all people with this condition. This recommendation needs further study because over the last 25 years, the global all-age prevalence of CKD has increased by 29% with nearly 700 million patients of all-stage CKD recorded in 2017 [53].…”
Section: Expanding the High-risk Groups For Tb Preventive Therapymentioning
confidence: 99%
“…Chronic kidney disease affects 700 million individuals worldwide and contributes to one in 20 deaths annually 1. Globally, the age standardised mortality rate attributable to CKD has remained virtually unchanged over the past decade, in contrast to most other non-communicable chronic diseases for which these rates have fallen 12. This seemingly intractable problem is driven largely by diabetes 1.…”
mentioning
confidence: 99%
“…Globally, the age standardised mortality rate attributable to CKD has remained virtually unchanged over the past decade, in contrast to most other non-communicable chronic diseases for which these rates have fallen 12. This seemingly intractable problem is driven largely by diabetes 1. It is thus not surprising that sodium glucose cotransporter 2 (SGLT2) inhibitors have garnered considerable attention following recent clinical trials showing consistent benefits of these glucose lowering drugs on major adverse kidney outcomes 3456…”
mentioning
confidence: 99%